Preparation of Magnetic-ZnO Nanocomposite by High Energy Milling Method for Methyl Orange Degradation - Didin S. Winatapura; Siti Wardiyati; Adel Fisli (Jurnal Kimia dan Kemasan, 2016)
A magnetic Fe3O4/ZnO nanocomposite (NCs) was prepared by a high energy milling (HEM) method. In the present study, the ZnO catalyst was prepared through two ways. The ZnO was synthesized by coprecipitation method (ZnO (S)), and ZnO directly used a commercial product (ZnO (Ald)). The prepared NCs were characterized using X-ray diffraction (XRD), vibrating sample magnetometer (VSM), Fourier transform infrared (FTIR), transmission electron microscope (TEM), and UV-Vis spectrophotometer. The XRD refinement indicates that Fe3O4 nanoparticle (NP) is a single phase and well indexed to cubic spinal structured magnetite. The Fe3O4/ZnO (S) and Fe3O4/ZnO (Ald) NCs are consisted of Fe3O4 and ZnO phases. The VSM result show that Fe3O4 NP, Fe3O4/ZnO (S), and Fe3O4/ZnO (Ald) NCs possess super-paramagnetic properties with saturation magnetization (Ms) is 102 emu.g-1, 28 emu.g-1 and 26 emu. g-1, respectively. The TEM observation shows that the average diameter of Fe3O4 is approximately 15 nm, while the thickness both of ZnO shell is ranging 20 nm - 50 nm. The average diameter of TiO2 P25 particle as catalyst was observed about 20 nm. The photocatalytic activity of catalysts were evaluated based on the degradation of methyl orange (MO) dye solution. The result shows that at pH = 7, the Fe3O4/ZnO (Ald) NC can degrade the pollutant in MO dye solution to 99 %, where as at pH = 3, the catalyst TiO2 P25 degrade only 96%.